2017
DOI: 10.1021/acsomega.7b01495
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed Ru Nanoparticles Functionalized Graphene Nanosheets as Efficient Cathode Catalysts for O2-Assisted Li–CO2 Battery

Abstract: In Li–CO 2 battery, due to the highly insulating nature of the discharge product of Li 2 CO 3 , the battery needs to be charged at a high charge overpotential, leading to severe cathode and electrolyte instability and hence poor battery cycle performance. Developing efficient cathode catalysts to effectively reduce the charge overpotential represents one of key challenges to realize practical Li–CO 2 batteries. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 39 publications
2
44
0
2
Order By: Relevance
“…The sluggish CO 2 reduction and evolution reactions that take place at the air cathode often impede the kinetics of Li–CO 2 batteries, leading to a high voltage (>4.5 V vs Li/Li + ) for decomposing the discharge product (Li 2 CO 3 ). [ 5–7 ] Under such a high anodic potential, the electrolyte oxidation limits the energy efficiency and cycling life of the Li–CO 2 batteries. [ 5–7 ] Therefore, efficient and robust cathode catalysts are required to promote their energy efficiency and cycle life by facilitating the reversible formation and decomposition of Li 2 CO 3 during the discharge/charge processes in Li–CO 2 batteries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sluggish CO 2 reduction and evolution reactions that take place at the air cathode often impede the kinetics of Li–CO 2 batteries, leading to a high voltage (>4.5 V vs Li/Li + ) for decomposing the discharge product (Li 2 CO 3 ). [ 5–7 ] Under such a high anodic potential, the electrolyte oxidation limits the energy efficiency and cycling life of the Li–CO 2 batteries. [ 5–7 ] Therefore, efficient and robust cathode catalysts are required to promote their energy efficiency and cycle life by facilitating the reversible formation and decomposition of Li 2 CO 3 during the discharge/charge processes in Li–CO 2 batteries.…”
Section: Methodsmentioning
confidence: 99%
“…[ 5–7 ] Under such a high anodic potential, the electrolyte oxidation limits the energy efficiency and cycling life of the Li–CO 2 batteries. [ 5–7 ] Therefore, efficient and robust cathode catalysts are required to promote their energy efficiency and cycle life by facilitating the reversible formation and decomposition of Li 2 CO 3 during the discharge/charge processes in Li–CO 2 batteries. [ 6,8 ]…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al also reported a low charge potential of 4.02 V and a good cycle stability (67 cycles with a fixed capacity of 500 mAh g −1 ) in the O 2 -assisted Li−CO 2 battery with the Ru/graphene nanosheets cathode. [62] That is to say, the presence of Ru helps to reduce the charge potential, which can avoid electrolyte decomposition in the operating potential range, and the Li-CO 2 cells can achieve excellent reversibility. Recently, Zhang et al indicated that the highly dispersed Ni nanoparticles on N-doped graphene (Ni-NG) could be used as an efficient cathode for Li-CO 2 batteries, with a discharge capacity of 17 625 mAh g −1 , and a cycle life of 100 cycles with a cutoff capacity of 1000 mAh g −1 at 100 mA g −1 .…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…The Li–O 2 /CO 2 batteries with high capacity provided a possibility to operate with Li 2 CO 3 as the main energy carrier, first proposed by Albertus et al Upon discharging, the total reaction is 4Li + + 4e − + 2CO 2 + O 2 → 2Li 2 CO 3 , where the number of electrons consumed per mole of gas is confirmed by DEMS . Yin et al investigated the discharge processes of Li–O 2 /CO 2 batteries (70%/30%), with Li 2 CO 3 as the final discharge product, in two solvents DMSO (DN = 29.8) and DME (DN = 24) .…”
Section: Other Energy Carriersmentioning
confidence: 99%